Evaluasi Layanan Taksi Menggunakan Agen Based Modeling (ABM) - Istiqomah, Silvi; Yuniaristanto, Y; Suletra, I Wayan (Jurnal Ilmiah Teknik Industri, 2019)
Taxi services involve the number of taxi and demand. A balance is needed for operated taxi and demand, so that the number of canceled order decreases. This system involves taxi and consumers as agents with various behaviors from their agents, then solved using modeling methods. Agent-based modeling is a feasible method used in this study because it can accommodate the properties and attributes of each agent. From the scenario that has been done, the average number of good fleets to operate is 103 fleets, with the canceled order rate is 1.2% and this model proves that the number of operated taxi is sensitive to the number of requests that exist.